Overexpression of catalase in mitochondria mitigates changes in hippocampal cytokine expression following simulated microgravity and isolation - Linda Rubinstein (Nature Portfolio, 2021)
Abstract Isolation on Earth can alter physiology and signaling of organs systems, including the central nervous system. Although not in complete solitude, astronauts operate in an isolated environment during spaceflight. In this study, we determined the effects of isolation and simulated microgravity solely or combined, on the inflammatory cytokine milieu of the hippocampus. Adult female wild-type mice underwent simulated microgravity by hindlimb unloading for 30 days in single or social (paired) housing. In hippocampus, simulated microgravity and isolation each regulate a discrete repertoire of cytokines associated with inflammation. Their combined effects are not additive. A model for mitochondrial reactive oxygen species (ROS) quenching via targeted overexpression of the human catalase gene to the mitochondria (MCAT mice), are protected from isolation- and/or simulated microgravity-induced changes in cytokine expression. These findings suggest a key role for mitochondrial ROS signaling in neuroinflammatory responses to spaceflight and prolonged bedrest, isolation, and confinement on Earth.